Chromite-PGM Mineralization in the Lherzolite Mantle Tectonite of the Kraka Ophiolite Complex (Southern Urals, Russia) - Giorgio Garuti (MDPI AG, 2021)
The mantle tectonite of the Kraka ophiolite contains several chromite deposits. Two of them consisting of high-Cr podiform chromitite—the Bolshoi Bashart located within harzburgite of the upper mantle transition zone and Prospect 33 located in the deep lherzolitic mantle—have been investigated. Both deposits are enveloped in dunite, and were formed by reaction between the mantle protolith and high-Mg, anhydrous magma, enriched in Al2O3, TiO2, and Na2O compared with boninite. The PGE mineralization is very poor (<100 ppb) in both deposits. Laurite (RuS2) is the most common PGM inclusion in chromite, although it is accompanied by erlichmanite (OsS2) and (Ir,Ni) sulfides in Prospect 33. Precipitation of PGM occurred at sulfur fugacity and temperatures of logƒS2 = (−3.0), 1300–1100 °C in Bolshoi Bashart, and logƒS2 = (−3.0/+1.0), 1100–800 °C in Prospect 33, respectively. The paucity of chromite-PGM mineralization compared with giant chromite deposits in the mantle tectonite in supra-subduction zones (SSZ) of the Urals (Ray-Iz, Kempirsai) is ascribed to the peculiar petrologic nature (low depleted lherzolite) and geodynamic setting (rifted continental margin?) of the Kraka ophiolite, which did not enable drainage of the upper mantle with a large volume of mafic magma.